2019
DOI: 10.1055/a-0919-3879
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Type 1 Iodothyronine Deiodinase by Bisphenol A

Abstract: Plastics are ubiquitously present in our daily life and some components of plastics are endocrine-disrupting chemicals, such as bisphenol A and phthalates. Herein, we aimed to evaluate the effect of plastic endocrine disruptors on type 1 and type 2 deiodinase activities, enzymes responsible for the conversion of the pro-hormone T4 into the biologically active thyroid hormone T3, both in vitro and in vivo. Initially, we incubated rat liver type 1 deiodinase and brown adipose tissue type 2 deiodinase samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…Transcriptional levels of deiodinases were more elevated in exposed zebrafish, in accordance with a study reporting that hypothyroidism caused by EDCs is associated with higher activity and expression of Dio2 [164]. On the other hand, a recent study reported a reduction of liver DIO1 activity in BPA-treated adult rats [102], which is a finding worth of note as decreased expression of DIO1 was observed in nearly all PTCs and is likely an early event in malignant TC [165].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Transcriptional levels of deiodinases were more elevated in exposed zebrafish, in accordance with a study reporting that hypothyroidism caused by EDCs is associated with higher activity and expression of Dio2 [164]. On the other hand, a recent study reported a reduction of liver DIO1 activity in BPA-treated adult rats [102], which is a finding worth of note as decreased expression of DIO1 was observed in nearly all PTCs and is likely an early event in malignant TC [165].…”
Section: Discussionsupporting
confidence: 87%
“…Adult males treated with BPA showed a decrease activity of hepatic DIO1, coherently with what has been reported in vitro [102]. Moreover, in female adult rats BPA lowered thyroid iodide uptake and thyroid peroxidase (TPO) activity, which are two essential steps in TH biosynthesis, probably due to an elevation of reactive oxygen species (ROS) production.…”
Section: Rodentssupporting
confidence: 85%
See 2 more Smart Citations
“…Bisphenols are also reported to bind to the α and β receptors of fatty tissues and modulate their functions. BPA exposure also disrupts thyroid signaling by affecting the metabolism of the thyroid hormone [101].…”
Section: Obesity and Diabetesmentioning
confidence: 99%